THE IMPACT OF MYCORRHIZAL PREPARATION MYKONET ON VALUABLE AGRONOMICAL AND ECONOMIC INDICATORS OF PEPPER (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The aim of the present study was to determine the effect of the Indian mycorrhizal preparation Mykonet (Mn) of Endo type on agronomical and economic indicators of the hot and sweet pepper production. The study was conducted with two sweet (Zmrukht and Nush-55) and two hot varieties of pepper (Kon and Punj). The experiments were carried out according to the block randomization method. It has been shown that Mn improves the biological and economic characteristics of sweet and hot peppers, depending on the treatment duration and variety. The most effective was 2 h treatment. The dry matter content was increased slightly, but increased for sugars and ascorbic acid. The best effect was obtained for Zmrukht. Given that Mn has improved the agronomical and economic characteristics of sweet and hot peppers, it can be recommended for pepper production.
Keywords: mycorrhiza; Mykonet; pepper; vegetable quality and yield; economic efficiency